Soil Quality Assessment under Restorative Soil Management Practices in Soybean (Glycine Max) after Six Years in Semi-Arid Tropical Black Lands of Central India. Issue 12 (3rd July 2016) - Sharma, K. L.; Chandrika, D. Suma; Grace, J. Kusuma; Shankar, G.R. Maruthi; Sharma, S. K.; Thakur, H. S.; Jain, M. P.; Sharma, R. A.; Chary, G. Ravindra; Srinivas, K.; Gajbhiye, Pravin; Venkatravamma, K.; et al.
ABSTRACT: Vertisol soils of central India are heavy in texture, with high clay content and low organic matter. These soils are prone to degradation and the soil loss is due to poor management practices including excessive tillage. Based on a long-term study conducted for improving the quality of these soils, it was found that management practice such as low tillage (LT) + 4 t ha −1 compost + herbicide (Hb) recorded significantly higher organic carbon (OC) (6.22 g kg −1 ) and available N (188.5 kg ha −1 ) compared to conventional tillage (CT) + recommended fertilizer (RF) + off-season tillage (OT) + hand weeding (HW) (OC: 4.71 g kg −1, available nitrogen (N) (159.3 kg ha −1 ). Among the physical soil quality parameters, mean weight diameter (MWD) was significantly higher under LT + 4 t ha −1 straw + Hb (0.59 mm). The practice of LT + 4 t ha −1 straw + HW recorded significantly higher microbial biomass carbon (MBC) (388.8 μg g −1 ). The order of key indicators and their contribution towards soil quality was as follows: OC (29%) >, MBC (27%) > available zinc (Zn) (22%) > MWD (9%) > available boron (B) (8%), > dehydrogenase activity (DHA) (5%). The order of the best treatment which maintained soil quality index (SQI) values reasonably good (>1.5) was as follows: LT + 4t ha −1 compost + HW (1.65) > LT + 4 t ha −1 compost +Hb (1.60) > LT + 4t ha −1 straw + HW (1.50). Hence, these treatments could be recommended to the farmers for maintaining higher soil quality in Vertisols under soybean system. Correlation studies revealed stronger relationship between key indicators like OC ( R 2  = 0.627), MBC ( R 2  = 0.884), available Zn ( R 2  = 0.739) and DHA ( R 2  = 0.604) with Relative Soil Quality Index (RSQI). The results of the present study would be highly useful to the researchers, farmers and land managers.